Late Cretaceous aquatic plant world in Patagonia, Argentina - Cúneo, Néstor Rubén; Gandolfo, María A.; Zamaloa, María del Carmen; Hermsen, Elizabeth (PLoS ONE)
In this contribution, we describe latest Cretaceous aquatic plant communities from the La Colonia Formation, Patagonia, Argentina, based on their taxonomic components and paleoecological attributes. The La Colonia Formation is a geological unit deposited during a Maastrichtian-Danian transgressive episode of the South Atlantic Ocean. This event resulted in the deposition of a series of fine-grained sediments associated with lagoon systems occurring along irregular coastal plains in northern Patagonia. These deposits preserved a diverse biota, including aquatic and terrestrial plants and animals. The aquatic macrophytes can be broadly divided into two groups: free-floating and rooted, the latter with emergent or floating leaves. Free-floating macrophytes include ferns in Salviniaceae (Azolla and Paleoazolla) and a monocot (Araceae). Floating microphytes include green algae (Botryoccocus, Pediastrum and Zygnemataceae). Among the rooted components, marsileaceous water ferns (including Regnellidium and an extinct form) and the eudicot angiosperm Nelumbo (Nelumbonaceae) are the dominant groups. Terrestrial plants occurring in the vegetation surrounding the lagoons include monocots (palms and Typhaceae), ferns with affinities to Dicksoniaceae, conifers, and dicots. A reconstruction of the aquatic plant paleocommuniy is provided based on the distribution of the fossils along a freshwater horizon within the La Colonia Formation. This contribution constitutes the first reconstruction of a Cretaceous aquatic habitat for southern South America. Fil: Cúneo, Néstor Rubén. Museo Paleontológico Egidio Feruglio; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Gandolfo, María A. Cornell University; Estados Unidos Fil: Zamaloa, María del Carmen. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución; Argentina Fil: Hermsen, Elizabeth. Ohio University; Estados Unidos